Laser-induced radial birefringence and spin-to-orbital optical angular momentum conversion in silver-doped glasses - Amjad, Jafar Mostafavi; Khalesifard, Hamid Reza; Slussarenko, Sergei; Karimi, Ebrahim; Marrucci, Lorenzo; Santamato, Enrico (Applied physics letters, 2011)
Samples of Ag + /Na + ion-exchanged glass that have been subject to intense laser irradiation may develop novel optical properties, as a consequence of the formation of patterns of silver nanoparticles and other structures. Here, we report the observation of a laser-induced permanent transverse birefringence, with the optical axis forming a radial pattern, as revealed by the spin-to-orbital angular momentum conversion occurring in a probe light beam. The birefringence pattern can be modeled well as resulting from thermally-induced stresses arising in the silver-doped glass during laser exposure, although the actual mechanism leading to the permanent anisotropy is probably more complex.